Basque Conflict and the Violence of ETA in Contemporary Spanish Graphic Novel: Study of four Cases - Vilches, Gerardo (Historia y Comunicación Social, 2022)
In the last years, Spanish graphic novel has paid special attetion to historical genre, particulary in respect of recent history. Concretely, many works which deal with Basque conflict and terrorist group ETA’s actions have been published. Through the application of an specific methodology, the critical reading of He visto ballenas (Javier de Isusi, 2014), Las oscuras manos del olvido (Felipe Hernández Cava and Bartolomé Seguí, 2014), Los puentes de Moscú (Alfonso Zapico, 2018) and Salto (Mark Bellido and Judith Vanistendael, 2019), works produced in the context of the end of the armed struggle of ETA, reveals different points of view, which underline the value of comic as a medium for the analysis of political reality.
Keywords: Comic; ETA; Graphic Novel; Basque Country; Terrorism